The Effect of Inflation, Exchange Rate, and Rubber Production on the Volume of Rubber Exports in the Islamic Economic Perspective in Indonesia - Wijayanti, Dwi; Budimansyah, Budimansyah; Devi, Yulistia (Indonesian Journal of Islamic Economics and Finance, 2025)
This work aims to analyze the influence of inflation, exchange rate, and rubber production on the volume of Indonesian rubber exports in the perspective of Islamic economics. Indonesia is one of the largest rubber producing countries in the world, with the rubber sector playing an important role in the national economy. Natural rubber commodity not only contributes to the country's revenue through export foreign exchange, but also absorbs large amounts of Labor and supports the downstream industry sector based on rubber raw materials. The work was conducted using panel data from ten major rubber-producing provinces in Indonesia during 2014 to 2023. The analysis method used is panel data regression with common effect, fixed effect, and random effect approaches. The outcomes showed that partially and simultaneously, the three independent elements have a significant influence on the volume of rubber exports. In the Islamic economic perspective, economic stability and Justice of distribution are important cornerstones in understanding the dynamics of export trade. This examination contributes to policy making that is fair and in accordance with Sharia principles in the management of Indonesia's export sector.